Resistance to coro stunt spiroplasm (CSS) due to infestations of Dalbulus maidis. - Hidalgo, Héctor; Castañón, Guillermo; Rodríguez, Flavio (Agronomía Mesoamericana, 2016)
A method consisting of infesting maize plants during their first fifteen days was used to detect CSS resistance sources. Four leafuoppers infested with the CSS complex were placed on each seedling. Highly significant differences were found among lines evaluated according to grain yield (p = 0,0001). The best lines were LT- 173 with 3,818 kg/ha, LT-183 with 3,808 kg/ha, and LT - 184 with 3,626 kg/ha. LT-183 and LT-184 did not show any CSS symptoms, and LT-173 had only chlorosis in leaf borders and phylodia [proliferation of leaves in the ear]. Two closelyrelated symptoms are leaf chlorosis and short intemode (r = 0.83), which also appear most frequently in the CSS syndrome (r = 0.45). Other variables affecting CSS are also discussed.